2019
DOI: 10.1007/s10853-019-04136-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of silver nanoparticles during synthesis of Ag–Au nanoalloy by UV irradiation method

Abstract: Formation of Ag-Au nanoalloy and self-organization of Ag nanoparticles into nanostructured wires under UV irradiation were reported in this work. This phenomenon was observed only in the presence of chloroauric acid. On the basis of the analysis of transmission electron microscope images and energydispersive X-ray spectroscopy, formation mechanism of nanostructured wires as well as of Ag-Au nanoalloy were proposed. The role of UV illumination and the presence of chloride ions were discussed. The UV-Vis spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…This coincides well with previous results (Kamli et al 2021). Figure 4b shows the SAED pattern which exhibits alternating dots and concentric rings, demonstrating that these NPs are polycrystalline (Łukowiec and Radoń 2020). SEM analyses showed that the particle shapes were spherically shaped, highly distributed, and polydisperse with uniform surfaces (Fig.…”
Section: Morphological Analysis Of Ag-febnpssupporting
confidence: 91%
“…This coincides well with previous results (Kamli et al 2021). Figure 4b shows the SAED pattern which exhibits alternating dots and concentric rings, demonstrating that these NPs are polycrystalline (Łukowiec and Radoń 2020). SEM analyses showed that the particle shapes were spherically shaped, highly distributed, and polydisperse with uniform surfaces (Fig.…”
Section: Morphological Analysis Of Ag-febnpssupporting
confidence: 91%
“…Other studies also showed the characterization of elemental composition of ZnONPs and their purity using EDX [53,54]. The formation of agglomerated spherically shaped AgNPs by the UV irradiation method have been reported previously [52]. However, there is no report which involves the C. equisetifolia leaf-extract-mediated synthesis of ZnONPs under the influence of UV-A and UV-C radiation.…”
Section: Energy-dispersive X-ray (Edx) Analysismentioning
confidence: 95%
“…Moreover, the different chemical structures of the polymers enable specific interactions with the metallic surface, triggering significant variations in the size and shape of the obtained metallic NPs [ 66 ]. Some studies have detailed the impact of various polymers on the characteristics of Ag NPs and Au NPs, such as poly(vinyl pyrrolidone) (PVP) [ 2 , 96 , 97 ], polymethacrylate (PMA) [ 98 ], poly-, mono-saccharides and proteins (chitosan, glucose, dextrose, gelatin) [ 41 , 89 , 94 , 96 ], sodium dodecyl sulfate (SDS) [ 99 ], and natural rubber (NR) latex [ 66 ]. Additionally, the experimental parameters determine the NP features and morphology, namely, the use and nature of the stabilizers, pH of the reaction medium, precursor concentration, exposure time, and, importantly, light source and wavelength [ 100 , 101 ].…”
Section: Photochemical Processesmentioning
confidence: 99%